Design of gearshift lever characteristics based on human arm mechanical properties - Kazuo NISHIKAWA; Kouji FURUKAWA; Isao KAWATE; Takahide NOUZAWA; Toshio TSUJI (Nihon Kikai Gakkai ronbunshu, 2014)
In the study reported here, the operational characteristics of a human-gearshift lever system were experimentally analyzed in consideration of the mechanical properties of the human arm and related effects on muscle activity. The results highlighted three points in particular: (1) It is possible to determine positioning that facilitates operation as well as the operational direction of the gearshift lever based on force manipulability in consideration of human joint-torque characteristics; (2) subjects feel that handling is easier when arm muscle activities in push and pull operations are almost equal during translational lever movement; and (3) the gearshift lever operation speed and the force-stroke characteristics have a very significant effect on whether operation is favorable or poor. Comprehensive consideration of these results is expected to be useful in the design of a human-vehicle gearshift lever system.